The Effects of Early Childhood Teachers’ Professional Development and Intrapersonal Intelligence on Their Teacher-Child Interactions - Minkyoung Lee; Sanglim Kim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Quality childcare and education play a significant role in the well-being of children (Kim & Yang, 2016). One of the vital factors of quality childcare and education is teacher-child interactions (Kim & Kim, 2020). The purpose of this study is to examine the professional development and intrapersonal intelligence of early childhood teachers on their teacher-child interactions. The sample comprised of 324 early childhood teachers in South Korea. The empirical data was collected by administering the Professional Development Scale for Early Childhood Teachers (Baik & Cho, 2004), the Adult Introspective Intelligence Scale (An & Oh, 2013), and the Teacher-child Interaction Scale (Lee, 2003). The collected data was analysed using SPSS 24.0, along with descriptive statistics, Pearson’s correlation analysis, and the analysis of multiple regressions. The results revealed statistically significant positive correlations between professional development, intrapersonal intelligence, and teacherchild interactions of early childhood teachers. Moreover, early childhood teachers’ professional development and intrapersonal intelligence statistically significantly affected their teacher-child interactions. This finding suggests that the professional development and intrapersonal intelligence of teachers should be supported and improved to increase the quality of teacher-child interactions. Theoretical and practical implications along with directions for further research are discussed.